Polycentric Governance for Defense Area Empowerment: The Concepts and Implications for the Universe Defense System - Wibowo, Irfan; Juwono, Vishnu (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
The universal defense system positions defense affairs as the joint task of all components of the nation. A good defense system will form a regional or global regional balance. Appropriate governance in empowering defense areas in the framework of forming a defense system as a form of state responsibility towards the people in guaranteeing sovereignty. This study uses the theory of polycentric governance which is conceptualized on empowering defense areas to create a universal defense system. The research method in this study used qualitative by digging up secondary data as a database for analysis carried out by reducing data, presenting data and drawing conclusions. The results of this study are that the governance of the empowerment of defense areas can be carried out in a polycentric manner involving many actors formed by the existence of overall polycentric governance rules, problem characteristics and heterogeneity. Furthermore, in the stages of polycentric governance, the empowerment of defense areas starts with the formation of a structure that creates collaboration between actors and in the end, a pattern of regular interaction that is polycentric is formed.